Long Intergenic Noncoding RNA MIAT as a Regulator of Human Th17 Cell Differentiation - Khan, Mohd Moin; Khan, Meraj Hasan; Kalim, Ubaid Ullah; Khan, Sofia; Junttila, Sini; Paulin, Niklas; Kong, Lingjia; Rasool, Omid; Elo, Laura L.; Lahesmaa, Riitta (Frontiers in Immunology, 2022)
T helper 17 (Th17) cells protect against fungal and bacterial infections and are implicated in autoimmunity. Several long intergenic noncoding RNAs (lincRNA) are induced during Th17 differentiation, however, their contribution to Th17 differentiation is poorly understood. We aimed to characterize the function of a lincRNA Myocardial Infarction Associated Transcript (MIAT) during early human Th17 cell differentiation. We found MIAT to be upregulated early after induction of human Th17 cell differentiation along with an increase in the chromatin accessibility at the gene locus. STAT3, a key regulator of Th17 differentiation, directly bound the MIAT promoter and induced its expression during the early stages of Th17 cell differentiation. MIAT resides in the nucleus and regulates the expression of several key Th17 genes, including IL17A, IL17F, CCR6 , and CXCL13, possibly by altering the chromatin accessibility of key loci, e.g., IL17A locus. Further, MIAT regulates the expression of PKC-α, protein kinase C alpha (PKCα), an upstream regulator of IL17A. A reanalysis of published single-cell RNA-seq data showed that MIAT was expressed in T cells from the synovium of RA patients. Our results demonstrate that MIAT contributes to human Th17 differentiation by upregulating several genes implicated in Th17 differentiation. High MIAT expression in T cells of RA patient synovia suggests a possible role of MIAT in Th17 mediated autoimmune pathologies.